Regional Economic Outlook, May 2006 : Asia and Pacific. (Regional Economic Outlook, 2006)
This report gives the IMF's view of the outlook for Asia, identifies the main risks to growth, and considers the key factors that will influence capital inflows. The REO also hones in on the policy challenges facing the region, especially the need to spur domestic demand, so that growth becomes more balanced and sustainable-and helps reduce the large global current account imbalances.